Black Diaspora Christian Activity in Britain from the Late Eighteenth Century to 1950. (September 2022) - Killingray, David
Abstract : Black men and women from across the Americas were a common feature of the British Christian scene in the nineteenth and early twentieth centuries. They came as missionaries en route to Africa, as fugitives from British or United States slavery and as suppliants for financial aid for black-led churches. Much transatlantic shipping, dominated by British vessels, came to British ports which served as transit points for further travel. Black travellers to Britain had indeterminate times of stay when often they were aided by white British patrons who provided opportunities for preaching, for further study, to acquire new skills, gain financial support, and in some cases to marry. And for black missionaries proceeding to Africa, Britain's pivotal location remained as a place for rest and recuperation, for the education of children, for medical care, deputation work, and for retirement. These processes and opportunities are analysed in this paper.